Employment of automation system in food canning of corn products - Ananthanathorn, Kant; Nukman, Yusoff; Tamrin, Khairul Fikri (ASEAN University Network (AUN/SEED-Net), 2012)
Canned foods industry is no longer regarded as a minor player in a global food sector. Canning food is useful to preserve the food quality and taste over a significantly long time period. In this paper, a feasibility study focuses on the employment of an automation system in food canning of corn products specifically at a loading station. A comprehensive data on input and output quantity of defect products was initially collected and studied. Process modeling and PLC programming were developed with aim at reducing such defects by converting the semi-automated mechanism into a fully-automated system. Substantial benefits have been obtained in terms of reduced quantity of defect products, saving in operating cost and reduction of manual staff number